Exploring the potential of reconfigurable platforms for order book update - He,C; Fu,H; Luk,W; Li,W; Yang,G (IEEE, 2017)
The order book update (OBU) algorithm is widely used in financial exchanges for rebuilding order books. The number of messages produced has drastically increased over time. The software solutions become more and more difficult to scale with the growing message rate and meet the requirement of low latency. This paper explores the potential of reconfigurable platforms in revolutionizing the order book architecture, and proposes a novel order book update algorithm optimized for maximal throughput and minimal latency. Our approach has three main contributions. First, we derive a fixed tick data structure for the order book that is easier to be mapped to the hardware. Second, we design a customized cache storing the top five levels of the order book to further reduce the latency. Third, we propose a hardware-friendly order book update algorithm based on the data structures we proposed. In the experiment, our FPGA-based solution can process 1.2-1.5 million messages per second with the throughput of 10Gb/s and the latency of 132-288 nanoseconds, which is 90-157 times faster than a CPU-based solution, and 5.2-6.6 times faster than an existing FPGA-based solution.